A multidimensional analysis of strategies for improving New Zealand residential construction productivity - Mark Kirby; Funmilayo Ebun Rotimi; Nicola Naismith (Ain Shams Engineering Journal)
The New Zealand residential construction sector faces significant quality-related challenges that hinder its productivity despite its significant impact on the national economy. This study uses a mixed-methods approach to evaluate the effectiveness of quality management as a strategy in improving New Zealand residential construction productivity. Data were collected from 106 of 305 questionnaires distributed by construction industry bodies. Key findings emphasise three improvement strategies: (1) implementing a productivity certification and training scheme, (2) addressing the industry’s prioritisation of time and cost over quality, and (3) enhancing quality management practices. The study confirms the ISO9000 quality management standards and Lean construction methods are widely supported as strategies for improving productivity. The study highlights the need for greater awareness of quality managements’ strategic value and the importance of government support and enhanced organisational leadership. Recommendations include the gradual implementation of ISO9000 quality management standards and the establishment of an industry-wide productivity training program. This study uniquely investigates New Zealand residential construction productivity, providing novel insights and recommendations for policymakers, industry professionals, organisations, and construction practitioners to align with global demand and improve productivity through enhanced quality.